2005
DOI: 10.25336/p66891
|View full text |Cite
|
Sign up to set email alerts
|

Panethnicity and Ethnic Resources in Residential Integration: A Comparative Study of Two Host Societies

Abstract: The racial and ethnic structure of a host society as well as its institutional and ideological context of integration shape the ethnic integration process. To examine these forces for residential integration, this study compares three panethnic groups in Canada and the United States using tabular data from the 2001 Canadian and the 2000 US censuses. Two ways in which the social context is important are identified. First, the social context affects how groups are distributed across urban neighbourhoods. As expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…But these researchers were interested in the effect of immigration on black-white segregation and as a result, did not investigate variation within and between panethnic groups. In a second study comparing segregation patterns in Canada and the United States, a range of ethno-national groups were classified according to panethnic grouping and the panethnic boundary was found to be meaningful for residential segregation (Kim 2005). Asian origin groups were more segregated than white ethnic groups in Canada but less segregated than white ethnic groups in the US.…”
Section: Segregation Panethnicity and Ethnic Differentiation: Backgrmentioning
confidence: 98%
See 1 more Smart Citation
“…But these researchers were interested in the effect of immigration on black-white segregation and as a result, did not investigate variation within and between panethnic groups. In a second study comparing segregation patterns in Canada and the United States, a range of ethno-national groups were classified according to panethnic grouping and the panethnic boundary was found to be meaningful for residential segregation (Kim 2005). Asian origin groups were more segregated than white ethnic groups in Canada but less segregated than white ethnic groups in the US.…”
Section: Segregation Panethnicity and Ethnic Differentiation: Backgrmentioning
confidence: 98%
“…To explain racial or ethnic residential patterns, three key theoretical perspectives are often considered; spatial assimilation theory, place stratification theory and the theory of ethnic retention (Kim 2005). The first two theories can be applied to explain panethnic residential patterns, that is, to explain why we might find ethno-national groups falling within a panethnic boundary to be less segregated from one another.…”
Section: Incorporating Panethnicity In Theories Of Residential Segregmentioning
confidence: 99%
“…In Australia, Pacific Islanders may position themselves at varying sites of social identity, sometimes identifying broadly as “Nesian”, sometimes identifying within a more specific ethno-national frame of reference (McGavin, 2014). A great strength of panethnicity as an analytical concept is that “it recognizes the layering of social identities, and ethnic and cultural diversity within constructed boundaries” (Kim, 2005, p. 3). Okamoto and Mora (2014) have observed that community leaders win more support when they depict panethnic identity as complementary to ethnic identity; thus successful panethnic organisation depends upon embracing, rather than denying or subsuming, ethnic diversity.…”
Section: Panethnic Organisation and Associationmentioning
confidence: 99%
“…How then to measure panethnic groupness? Manifestations that can be observed include panethnic protests and collective action (Okamoto, 2003; Espiritu, 1992; Mora, 2014), residential spatial segregation of ethnic and panethnic groups (Kim, 2005; Kim and White, 2010) and the existence of panethnic media or panethnic organisations (Okamoto, 2006; Mora, 2014; Itzigsohn, 2004). However, Okamoto has also demonstrated that the establishment of panethnic organisations is not a necessary precondition for panethnic activities or collective representation.…”
Section: Panethnic Organisation and Associationmentioning
confidence: 99%
See 1 more Smart Citation